2001
DOI: 10.1097/00003246-200112000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical aspiration-related practice patterns in the intensive care unit: A physician survey

Abstract: Our study revealed a divergent approach to antimicrobial treatment of cases of aspiration in the intensive care unit. Further investigation is warranted to determine why empirical antimicrobials are initiated frequently for noninfectious stages of aspiration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 21 publications
1
20
0
2
Order By: Relevance
“…Antibiotic use in our patient group was haphazard, with variation in initiation, duration, and antibiotic agent used. This is consistent with a recent survey of critical care physicians in the United States that demonstrated a divergent approach to antibiotic use in aspiration pneumonitis (24). The mainstay of treatment for aspiration pneumonitis is respiratory support (ventilation or noninvasive respiratory support), oxygen therapy, aggres- sive chest physiotherapy, and management of secondary complications.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Antibiotic use in our patient group was haphazard, with variation in initiation, duration, and antibiotic agent used. This is consistent with a recent survey of critical care physicians in the United States that demonstrated a divergent approach to antibiotic use in aspiration pneumonitis (24). The mainstay of treatment for aspiration pneumonitis is respiratory support (ventilation or noninvasive respiratory support), oxygen therapy, aggres- sive chest physiotherapy, and management of secondary complications.…”
Section: Discussionsupporting
confidence: 88%
“…The ORs and corresponding 95% CIs for each predictor, obtained from univariate logistic regression, are shown in Table 3. Of 441 patients with a GCS of Ն8, forty developed aspiration pneumonitis (9%; 95% CI, 7-12) compared with 24 of 144 patients with a GCS of Ͻ8 (17%; 95% CI, [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. A logistic regression model was constructed to predict aspiration pneumonitis in ICU patients with overdose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of treating ventilator associated Pneumonia (VAP), a short course of antibiotics has not been shown to have adverse effects as long as the antibiotics are deescalated or discontinued based on quantitative microbiology. Moreover, a recent survey suggested that a vast majority of intensivists were prescribing antibiotics in patients with suspected aspiration events(66). A rational strategy would be to start antibiotics appropriate to cover VAP (depending on the duration of stay in the ICU) and de-escalate the antibiotic use based on appropriate definitive, quantitative cultures (usually within 72 hrs).…”
Section: Management Principlesmentioning
confidence: 99%
“…Die ᭤Aspiration von saurem Magensaft, beispielsweise bei Einleitung einer Vollnarkose, ruft eine chemische Schädigung der Lunge hervor und stellt per se keine Indikation zur Gabe von Antibiotika dar [127], auch wenn dies -oft wider besseren Wissens -eine häufige Vorgehensweise in Kliniken ist [152]. Demgegenüber muss bei einer ᭤Aspiration von Darminhalt, beispielsweise bei obstruktivem Ileus oder bei Aspiration im Rahmen ausgedehnter tumoröser Prozesse im Mund oder Pharynx oder bei sehr schlechtem Zahnstatus, mit der Beteiligung anaerober Bakterien gerechnet werden.…”
Section: Aspirationspneumonieunclassified